Analisis Kemampuan Mahasiswa PGSD UNUGHA dalam Menyusun Rencana Pelaksanaan Pembelajaran IPA Kelas Atas sesuai Standar Kurikulum 2013 - Rahayuni, Galuh; Muniriyanto, Muniriyanto (Jurnal Pancar, 2017)
The aim to the reasearch is to know the student competency to design Science Lesson Plan based on Kurikulum 2013 standar. The kind of the research is descriptif-kuantitatif. Population of this reseach is all of PGSD student, and the amount of sample in this reseach is 15 which chosen with random sampling technique. Data collection technique is review document. The istrument which used in this reaseach is lesson plan check list document based on Kurtilas standar. ??The result show that 60% student in good standar, 20% in very good standar, 13% in enough standar, and 7% in less standar.